Peningkatan Efisiensi Pakan dan Performa Pertumbuhan Ikan Betok (Anabas testudineus) yang Dipelihara pada Periode Pemuasaan yang Berbeda - Fitrani, Mirna; Amin, Mohamad; Rismoni, Indah; Wijayati, Marini; Septimesy, Annisa; Mulyani, Yenni Sri; Mukti, Retno Cahya (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Fish feed is known to account for 60-70% of total aquaculture costs, posing a significant challenge to farmers. To address the issue, this study explored the effectiveness of periodic starvation in improving feed efficiency and growth performance of climbing perch while reducing the cost of purchasing feed. The method used was a completely randomized design (CRD) analyzed using ANOVA. Four treatments were applied with three replicates each. The treatments consisted of P0 (no fasting), P1 (one day of fasting followed by one day of feeding), P2 (one day of fasting and two days of feeding), and P3 (one day of fasting and three days of feeding). The parameters observed included feed efficiency, growth in length and absolute weight, and fish survival rates. The results showed that periodic starvation significantly impacted the absolute body weight growth and feed efficiency (P<0.05). However, no effect was observed on the survival rates and absolute length growth. Among the treatments, P1 showed the best results, with feed efficiency of 21.87%, length growth of 0.23 cm, weight growth of 0.22 g, and survival rate of 100%. In conclusion, this study found that periodic starvation combined with feeding could significantly improve fish feed use efficiency and save fish farmers' costs.